Technological innovation and personalized surgical treatment for early-stage endometrial cancer patients: A prospective multicenter Italian experience to evaluate the novel percutaneous approach. (March 2019) - Gueli Alletti, S.; Cianci, S.; Perrone, E.; Fanfani, F.; Vascone, C.; Uccella, S.; Gallotta, V.; Vizzielli, G.; Fagotti, A.; Monterossi, G.; Scambia, G.; Rossitto, C.
Abstract: Objective: To investigate the safety, feasibility and oncological adequacy of the Percutaneous Surgical System - PSS in a consecutive series of low-risk endometrial cancer staging. Study Design: From May 2015 to April 2017, we prospectively performed 30 consecutive percutaneous staging for low/intermediate risk endometrial cancer (FIGO stage IA G1-G2, IB G1-G2, IA G3). All patients were divided in two different groups on the basis of surgical procedure received: Group A included patients submitted to radical Class A hysterectomy and bilateral salpingo-oophorectomy; Group B concerned patients that received a lymph nodal assessment also. Results: The time needed to install percutaneous instruments and suprapubic trocar was 4 min. (range 2–10). The recorded median operative time (OT) was 80 min. (range 65–120) for Gr.A and 143 min. (range 107–190) for Gr.B, in which the median time of lymph nodal assessment was 55 min. (range 20–76). The median time for hysterectomy was 60 min. (range 40–110) in all cases. Lymph nodal assessment was performed in 14 (46.6%) cases: 7 sentinel node mapping, 7 pelvic lymphadenectomy. No intraoperative complications or LPS/LPT conversions were recorded. Median discharge time was 2 days (range 1–4), 5 patients were discharged in 3rd post-op day, and only 1 patient was discharged in 4th day for fever. All patients conveyed high satisfaction with the cosmetic results. A progressive overall reduction of pain perception was observed at 24 h after surgery. Median follow-up was of 14 months (range 12–36), no recurrences have been detected. Conclusions: PSS seems to be a feasible approach for endometrial cancer staging. Larger experiences and prospective comparative studies are important to assess our assumptions and further investigate the real benefits of percutaneous surgical system.